Designing Information Technology Governance in the Data Management Process Using Cobit Framework V 4.1 At the Pamulang University IT Center - Zein, Afrizal (Journal of Information System, Technology and Engineering, 2024)
This paper explores the implementation of Information Technology (IT) governance in the data management process using the Control Objectives for Information and Related Technologies (COBIT) framework version 4.1 at the IT Center of Pamulang University.  The study begins by providing an overview of the COBIT framework and its relevance to IT governance in educational settings. It then delves into the specific application of COBIT V 4.1 in the context of data management processes at Pamulang University IT Center. This includes the identification of key control objectives and control practices within the COBIT framework that are applicable to data management, such as data governance, data quality management, data security, and data lifecycle management. Furthermore, the paper discusses the methodology used for implementing COBIT V 4.1 in the data management process, including the steps involved in assessing current practices, identifying areas for improvement, and designing governance structures and processes. It highlights the importance of collaboration between IT professionals, data stewards, and organizational leadership in ensuring the successful implementation of IT governance practices. The findings of the study reveal the benefits of adopting COBIT V 4.1 in the data management process at Pamulang University IT Center, including improved data quality, enhanced data security, and increased accountability and transparency in data handling practices.